« LA PERCEPTION COMMUNAUTAIRE DE LA POPULATION SUR L’EPILEPSIE : CONNAISSANCE ET ATTITUDE DES FEMMES MARCHANDES DE LA VILLE D’ISIRO A PROPOS DE 120 INTERROGES DANS LE MARCHE DE CFU DU 04 AU 10 JUILLET 2019 » - Venant, YATWA ZANIWE Roger (IJRDO - Journal of Social Science and Humanities Research, 2022)
Epilepsy, a chronic disease, is one of the most common neurological disorders in the world. In the town of Isiro, capital of the Haut-Uélé province in the Democratic Republic of Congo, data on epilepsy cases are not available. Thus the choice of this topic is based on the fact that the community is not sufficiently aware of epilepsy. The population is not well equipped in understanding epilepsy, and still has too many prejudices and dangerous attitudes towards epilepsy patients. In the community of Isiro, it is the woman who cares most for family members who fall ill. Therefore, the present study aimed to assess the knowledge of women traders about epilepsy and to describe their attitudes towards an epileptic patient.It is a cross-sectional study, which took place from 07 to 10 July 2019, at the Chemin de Fer de l'Uélé (CFU) market, with 112 women traders who agreed to answer the survey questionnaire and they constituted the study sample. At the end of this study, it was found that 51% were of the Catholic religion, with a predominantly secondary education level of 48.2%.  The population had few epileptics in the family, 8%. All the respondents had heard of epilepsy, i.e. 100%. The main source of information was the family, 44.7%. Most of the subjects said that epilepsy was contagious, 66.9%.Many could not name an anti-epileptic drug, 91.9%. Some said that the epilepsy was due to a demonic cause or evil genius, 43.7%. Many said that in case of a seizure the patient runs the risk of injury, 46.4%. The majority said that epilepsy affects all categories of the population, 89.3%. Most of them said that the epileptic can study and get married, 58% and 60% respectively. The majority of respondents agreed that epilepsy is treatable and can be cured permanently, 90.1% and 80.3% respectively. Some of them (30.3%) mentioned intellectual disability and frequent seizures as complications of epilepsy if not treated. Many of them had already attended an epileptic seizure, 88.4%. Most of them had never performed a rescue action during a seizure, 75.9%. The majority said that they would stay away from a seizure to avoid contamination, 66.9%. Some cited prayer as the most effective means of recourse to control epileptic seizures, 36.6%.In conclusion: knowledge of epilepsy is still insufficient, and certain attitudes adopted towards epilepsy are not beneficial.